One-step preparation of iodine-doped graphitic carbon nitride nanosheets as efficient photocatalysts for visible light water splitting. Issue 8 (26th January 2015) - Han, Qing; Hu, Chuangang; Zhao, Fei; Zhang, Zhipan; Chen, Nan; Qu, Liangti
Abstract : A highly efficient visible-light-driven photocatalyst based on iodinated graphitic carbon nitride nanosheets (IGCNSs) has been prepared by facilely ball-milling graphitic carbon nitride (GCN) in the presence of iodine. Abstract : Here, a highly efficient visible-light-driven photocatalyst based on iodinated graphitic carbon nitride nanosheets (IGCNSs) has been prepared by facilely ball-milling graphitic carbon nitride (GCN) in the presence of iodine. With an iodine atomic content of 0.34 at%, the optimized IGCNSs sample shows a high H2 -production rate of 44.5 μmol h −1 under visible light illumination.